Analisis dan Rancangan Pola Peledakan pada Lapisan Interburden K37 – K39untuk Mendapatkan Fragmentasi yang Sesuai dengan Alat Muat di PT. Asmin Koalindo Tuhup, Kalimantan Tengah - Suhendrinal Suhendrinal; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2018)
Abstract.PT. Asmin Koalindo Tuhup is one of the industries engaged in coal mining, which is located in the Central Kalimantan region. Karaketeristik of cover rock in the area pit 7 and pit 8 interburden K37 and K39 with a thickness of 27 meters with different layers of mudstone material, siltstone and sandstone. The average thickness of the siltstone material is 3-5 meters and its position is in the upper layer which will be used as a stemming column during blasting. So that it is very influential on the results of blasting later, so it is necessary to do a blasting design to minimize the impact due to the condition of the layer. In the first actual blasting, >1 meter fragmentation value 31.69%, actual blasting of second fragmentation values ≥ 1 meter 26.8% and actual blasting of the third fragmentation value ≥ 1 meter 17.9%. Of the three results of the blasting it was not in accordance with the results of targeted fragmentation (≤ 15%). To minimize the results of the test, the geometry of the blasting is carried out. Based on the results of the study obtained the results of analysis and improvement on the proposed blasting pattern obtained mentasi 1 meter fragmentation using the calculation of wipfrag 0 software from the three proposals. The percentage of boulder ≤ 60 cm based on Kuzram has been below the target of 15% with a value of 6.57%, 6.45% and 6.16%. The digging time value has been below the company's target of 12 seconds, with a value of 10.21 seconds, 9.42 seconds and 10.45 seconds from the performance of the Liebherr R 9250 excavator excavator.Keywords:blasting, fragmentation, design, boulder, coal